SIMILARITIES AND DIFFFERENCES IN THE STATUS OF FORCED HEIRS ON THE TERRITORY OF THE FORMER REPUBLIC OF YUGOSLAVIA - Vidić Trninić, Jelena (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
This paper provides a comparative review on the existing legislation which regulates the status of forced heirs in legal systems on the territory of former Yugoslavia (Serbia, Montenegro, Slovenia, Croatia, Macedonia, Bosnia and Herzegovina and Republic of Srpska). The paper gives an overview of the persons that are eligible for forced heirship, conditions for being recognized as forced heir, size of the forced share, as well as influence of the size of the legal shares on the position of forced heirs. Special attention is given to the analysis of the influence of possible changes in the size of legal shares of inheritance on the size of shares belonging to forced heirs. In this context it is concluded that legal status of forced heirs in most countries which belong to this group, is up to a certain extent specific compared to the one in most other contemporary European legal systems, primarily because of its volatile character. Simultaneously, it is observed that, regardless of a common legal background and inherited similarities dating from the former joint state, there are significant differences between the analyzed legal systems concerning the legal status of forced heirs. Through this comparative review, the author strives to point out the advantages and disadvantages of the legal provisions existing in legislation of these countries. In this aspect, the author expresses the opinion whether there is a need for modification in national legislation regarding the analyzed aspects of the regulated status of forced heirs.